Environmental activist - Gleason, Carrie, 1973- (Get involved!, 2010)
Discusses environmental rights and activism, covering the various actions an activist can take; problems with waste, pollution, and consumption of fossil fuels; and principles of sustainability that people can utilize to be more environmentally friendly.